2006
DOI: 10.1055/s-2005-865814
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Performance in Three Types of Training Test in Swimming

Abstract: A variety of testing procedures are used to assess the effects of particular treatments on the training status of athletes. The present study aims to investigate the reproducibility of selected tests in swimming. Sixteen trained swimmers performed three kinds of test: 1) Constant Distance Test (CDT), 2) Constant Time Test (CTT), and 3) Constant Velocity Test (CVT). The analysis of the reproducibility was based on a test-retest procedure. The test-retest performances were highly correlated for the three kinds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 31 publications
4
30
0
2
Order By: Relevance
“…hese have traditionally been shown to have poor reliability with coeicients of variation ranging from 15.1 to 25% [7,8] Similar indings have been reported in both cycling [9] and swimming [10]. Hinckson and Hopkins [17] used a variety of approaches to produce estimates of test-retest error of measurement calculated from times to exhaustion.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…hese have traditionally been shown to have poor reliability with coeicients of variation ranging from 15.1 to 25% [7,8] Similar indings have been reported in both cycling [9] and swimming [10]. Hinckson and Hopkins [17] used a variety of approaches to produce estimates of test-retest error of measurement calculated from times to exhaustion.…”
Section: Discussionmentioning
confidence: 79%
“…Constant speed trials have been shown to have poor reliability with coeicients of variation ranging from 15.1% to 25% [7,8]. his is supported by similar research in both cycling and swimming, which also demonstrated the poor reliability of constant power/speed trials [9,10]. However, research into the reliability of the CS and ARC parameters is limited.…”
Section: Introductionmentioning
confidence: 95%
“…No timeto-exhaustion tests conducted with these particular constraints had been reported in the literature before, and further studies might help to confirm this range of values. Indeed, variability in the duration of this kind of exercise has been recently reported (Alberty et al, 2006). However, for each time-to-exhaustion test, the mean differences between the two sets were always greater than the variability reported by Alberty et al (2006) -that is, 6.6%.…”
Section: Analysis Of the ''Controlled'' Setmentioning
confidence: 76%
“…Indeed, variability in the duration of this kind of exercise has been recently reported (Alberty et al, 2006). However, for each time-to-exhaustion test, the mean differences between the two sets were always greater than the variability reported by Alberty et al (2006) -that is, 6.6%. Our results thus demonstrate the impact there might be on duration of constant-speed swims when imposing a given stroke rate.…”
Section: Analysis Of the ''Controlled'' Setmentioning
confidence: 76%
“…Variables used for the training prescription should be highly reproducible to ensure that individual measures are accurate and capable of monitoring training [7]. Conversely, low reproducibility of HR and RPE could result in errors in training zones [8].…”
Section: Introductionmentioning
confidence: 99%